2023
DOI: 10.1111/cns.14077
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota‐astrocyte axis: Implications for type 2 diabetic cognitive dysfunction

Abstract: Background Diabetic cognitive dysfunction (DCD) is one of the most insidious complications of type 2 diabetes mellitus, which can seriously affect the ability to self‐monitoring of blood glucose and the quality of life in the elderly. Previous pathological studies of cognitive dysfunction have focused on neuronal dysfunction, characterized by extracellular beta‐amyloid deposition and intracellular tau hyperphosphorylation. In recent years, astrocytes have been recognized as a potential therapeutic target for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 188 publications
(348 reference statements)
0
5
0
Order By: Relevance
“…DCI is a neurodegenerative disease caused by diabetes and is characterized by dysfunction in cognitive functions such as verbal and visual memory, information processing speed, and executive function (Ahmed et al, 2020). Studies have revealed that diabetes increases the risk of cognitive impairment by a factor of 1.25–1.91 and that cognitive dysfunction in diabetes is present in all age groups, and hyperglycemia and hyperlipidemia are the key driving factors (Li et al, 2023; Nie et al, 2022). Previous studies have shown that long‐term hyperglycemia in diabetic patients can lead to inflammation in the body, resulting in multiple organ damage (Khazaei et al, 2021; Rohm et al, 2022), suggesting that the inflammation may be a major cause of diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DCI is a neurodegenerative disease caused by diabetes and is characterized by dysfunction in cognitive functions such as verbal and visual memory, information processing speed, and executive function (Ahmed et al, 2020). Studies have revealed that diabetes increases the risk of cognitive impairment by a factor of 1.25–1.91 and that cognitive dysfunction in diabetes is present in all age groups, and hyperglycemia and hyperlipidemia are the key driving factors (Li et al, 2023; Nie et al, 2022). Previous studies have shown that long‐term hyperglycemia in diabetic patients can lead to inflammation in the body, resulting in multiple organ damage (Khazaei et al, 2021; Rohm et al, 2022), suggesting that the inflammation may be a major cause of diabetes and its complications.…”
Section: Discussionmentioning
confidence: 99%
“…Ruminococcaceae_ UCG-009 Turicibacter hyperglycemia and hyperlipidemia are the key driving factors (Li et al, 2023;Nie et al, 2022). Previous studies have shown that longterm hyperglycemia in diabetic patients can lead to inflammation in the body, resulting in multiple organ damage (Khazaei et al, 2021;Rohm et al, 2022), suggesting that the inflammation may be a major cause of diabetes and its complications.…”
Section: Odoribactermentioning
confidence: 99%
“…The gut and brain are closely connected through the gut brain axis. The brain-gut axis plays an important role in the information exchange system (Li et al, 2023). There is a complex two-way communication system between the central nervous system and the gastrointestinal system (Xu et al, 2022).…”
Section: Brain-gut Axis and Pocsmentioning
confidence: 99%
“…Moreover, an altered composition of the gut microbiota was observed in mouse models of traumatic brain injury [ 30 ], AD [ 31 ], and PD [ 21 ], also characterized by the presence of reactive astrogliosis. Recently, a research group demonstrated that a “gut microbiota-astrocyte” axis mediates neurocognitive dysfunctions secondary to metabolic disorders in diabetes mellitus [ 32 ].…”
Section: Gut–glia Axis In Brain Physiology and Pathology: Modulation ...mentioning
confidence: 99%
“…Evidence also demonstrates that recovery from gut dysbiosis via different strategies, including probiotics administration and FMT, is able to reverse the pathological activation of astrocytes [ 25 , 32 ].…”
Section: Gut–glia Axis In Brain Physiology and Pathology: Modulation ...mentioning
confidence: 99%